KINETIC STUDIES OF Cu ADSORPTION FROM SASIRANGAN LIQUID WASTE USING RICE HUSK ACTIVATED CARBON - Isna Syauqiah; Desi Nurandini; Nopi Stiyati Prihatini; Jamiyaturrasidah Jamiyaturrasidah (Konversi, 2021)
The industry of sasirangan – traditional fabric of Banjar Tribe – has been one of prime commodities of South Kalimantan. The coloring process  in sasirangan production used a lot of chemical elements containing heavy metals  and its waste potentially pollute the environment. One of the heavy metal waste contained is copper (Cu) which is toxic to aquatic organisms and humans. The treatment for sasirangan liquid waste can be done by adsorption process using activated carbon as adsorbent. This study aims to determine the appropriate kinetic model for adsorption of Cu metal from sasirangan liquid waste using activated carbon adsorbent made from rice husks.The process was conducted by batch system with chemical and physical activation. Chemical activation was done by soaking the activated carbon of rice husk with HCl solution for 24 hours. While physical activation was carried out by burning in a furnace at 500̊C for 2 hours. The adsorption treatment was given on sasirangan waste samples with variations on contact time (30, 60 and 120 minutes). The results of kinetics study showed that the adsorption process of Cu from sasirangan liquid waste onto rice husk activated carbon adsorbent followed first-order reaction kinetics with a correlation coefficient value (R2) of 0.96 and adsorption rate constant (k1) of 0.0044 min-1.